The Effectiveness of Islamic Economic Law in The Application of the Halal Value Chain (HVC) Ecosystem in the Halal Food and Beverage Industry in Indonesia - Barri, Abdul; Hadiat, Hadiat; Al-Hakim, Sofian; Hakim, Atang Abdul (Faculty of Law, Universitas Pekalongan, 2024)
Indonesia's potential in the halal industry at this time is very calculated, because Indonesia is the country with the largest Muslim population in the world. This role should not only be seen as a captive market, but also should encourage the growth of the halal industry in Indonesia that is able to compete globally. But in reality, currently Indonesia's halal food and beverage industry has not been included in the top 10 countries with the best halal food and beverage performance in the world. Whereas on the other hand, Indonesia actually has a great opportunity to develop halal products in this sector. The purpose of this study is to determine the effectiveness of Islamic economic law in the application of the halal value chain (HVC) ecosystem in the halal food and beverage industry in Indonesia. This research method uses a qualitative type of research with a descriptive analysis approach. The implementation of this researchwas carried out at food and beverage companies in Indonesia. The subject of the study was the Head of General Affairs of halal food and beverage managers and halal food and beverage employees in Indonesia. The subject was taken by purposive sampling. The researcher's goal is to take the problems that exist in the Indonesian halal food and beverage industry by implementing the Halal Value Chain ecosystem. Data collection techniques were carried out by observation, interviews, and questionnaires conducted to the Head of General Affairs of the food and beverage industry. The results of this study show that based on data from the Central Stastistic Agency (BPS) related to the Data on the Number of Halal Food and Beverage Exports in 2022 After the implementation of HVC shows that there is an increase in the export process and a reduction in the Import process, this means that the application of HVC in halal food and beverages in Indonesia is very influential so that it can increase the effectiveness of the halal product even though it has not fully run optimally. The supporting factors for the success of HVC are government support, dedicated assets, information technology, human resource management, collaborative partnerships, halal certification and halal traceability